Quality of life, support and smoking in advanced lung cancer patients: a qualitative study. Issue 1 (30th April 2014) - Rowland, C; Danson, S J; Rowe, R; Merrick, H; Woll, P J; Hatton, M Q; Wadsley, J; Ellis, S; Crabtree, C; Horsman, J M; Eiser, C
Abstract : Background: Lung cancer is the most common cancer and smoking is the principal cause. Due to poor survival rates, symptom palliation and promotion of health-related quality of life (HRQoL) are primary outcomes for lung cancer patients. Given the established relationship between smoking and lung cancer, patients who have smoked may feel stigmatised or guilty after diagnosis, and more pessimistic about their illness and likely outcomes. This may have adverse implications for HRQoL. Objectives: We explored HRQoL and support experiences among newly diagnosed patients with advanced lung cancer. Design: Semistructured interviews were conducted with nine patients and analysed using interpretative phenomenological analysis. Results: Patients described the physical, emotional and social impact of disease on HRQoL. Fear of compromising their immune system and adjusting to new relationship roles had a wide-ranging effect on patients' HRQoL. Patients acknowledged links between lung cancer and smoking but some continued to smoke. They were sensitive to the opinions of medical staff about smoking especially those who continued to smoke or recently quit. Conclusions: We conclude that staff should give clearer advice about the adverse implications of continued smoking. We discuss the potential value of diagnosis as a teachable moment for promoting smoking cessation among patients and family members.